2016
DOI: 10.1097/opx.0000000000000745
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Nerve Fiber Layer Thickness Alteration in Apneic Children

Abstract: Upper airway obstruction and OSAS seem to worsen some RNFL and IOP parameters in children, and eye examinations may be useful in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(29 citation statements)
references
References 22 publications
0
29
0
Order By: Relevance
“…43 It has also been indicated that RGCs are more sensitive to ischemia than the more distal retinal cells. 44,45 Retinal hypoxia leads to increase in some mediators including vascular endothelial growth factor, nitric oxide, glutamate, inflammatory cytokines, and reactive oxygen species. Enhanced expression of these mediators causes RGCs loss by disruption of blood retinal barrier, excitotoxicity, and increased accumulation of intracellular Ca 2+ .…”
Section: Discussionmentioning
confidence: 99%
“…43 It has also been indicated that RGCs are more sensitive to ischemia than the more distal retinal cells. 44,45 Retinal hypoxia leads to increase in some mediators including vascular endothelial growth factor, nitric oxide, glutamate, inflammatory cytokines, and reactive oxygen species. Enhanced expression of these mediators causes RGCs loss by disruption of blood retinal barrier, excitotoxicity, and increased accumulation of intracellular Ca 2+ .…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we used a simple utility in a website to combine sample size, mean, and standard deviation from multiple groups into 1 group instead of excluding the study. In the premier of this analysis, we included 2 studies[ 22 23 ] that the research objects were children with chronic upper airway obstructions (UAOs)/obstructive sleep apnea syndrome (OSAS) and children with sleep-disordered breathing. From the heterogeneity test results, P values of total, mild, and moderate OSAS were 0.024, 0.511, and 0.257, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Retina and optic nerve have been examined in OSAS paediatric patients with adenotonsillar hypertrophy with controversial results. Cinici and Tatar [10] found no signi cant alterations of RNFL thickness, while Simsek et al [11] showed that OSAS seems to in uence RNFL and IOP parameters. Both studies highlighted the potential risk of long-term optic injury due to blood intermittent hypoxia and recommend prompt treatment of OSAS in young people.…”
Section: Discussionmentioning
confidence: 96%
“…We examined children assessed for OSAS by overnight RP, to investigate for early signs of ocular changes related to airway obstruction during sleep, poorly documented and understood in the previous literature [10][11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation